2020
DOI: 10.21776/ub.jels.2019.010.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Reproductive Status in Ongole Crossbred (PO) Cow Based On Vaginal Epithel Morphology and Profile Hormone

Abstract: Hormonal fluctuations in livestock will affect vaginal cytology good overview on the condition of estrous until pregnancy. The purpose of this study was to determine the physiological condition of Ongole crossbred (PO) cow during estrous and determine pregnancy by the description of vaginal epithelial cells, progesterone, and estrogen hormone profiles. The materials were used 35 cows with physiological status (estrous, 5th pregnancy period, 16th pregnancy period, 22nd pregnancy period, and 60th pregnancy perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Also, at oestrus stage, vaginal smears were characteristically, highly cellular and consisting predominantly of superficial nucleated cells followed by anucleated superficial cells. These findings corroborate with the observations, in rats (Cora et al, 2015;Mohammed and Sundaram, 2018), in bitches (Pérez et al, 2005;Peña-Corona et al, 2019), in humans (Berga et al, 2019), in cows (Indira et al, 2014;Widyaningrum and Marhendra, 2020), in ewes (Solis et al, 2008;Zohara et al, 2014) and, in does (Fatet et al, 2010;Sitaresmi et al, 2018). Apparently, less leucocytes are encountered in this stage, which is at variance with the findings and observations of (Akusu, 1987;Ola et al, 2006) in a related breed: West African dwarf [WAD] does, depicting that mainly leucocytes and small epithelial cells were present at the oestrus stage.…”
Section: Vaginal Exfoliative Cytologysupporting
confidence: 88%
“…Also, at oestrus stage, vaginal smears were characteristically, highly cellular and consisting predominantly of superficial nucleated cells followed by anucleated superficial cells. These findings corroborate with the observations, in rats (Cora et al, 2015;Mohammed and Sundaram, 2018), in bitches (Pérez et al, 2005;Peña-Corona et al, 2019), in humans (Berga et al, 2019), in cows (Indira et al, 2014;Widyaningrum and Marhendra, 2020), in ewes (Solis et al, 2008;Zohara et al, 2014) and, in does (Fatet et al, 2010;Sitaresmi et al, 2018). Apparently, less leucocytes are encountered in this stage, which is at variance with the findings and observations of (Akusu, 1987;Ola et al, 2006) in a related breed: West African dwarf [WAD] does, depicting that mainly leucocytes and small epithelial cells were present at the oestrus stage.…”
Section: Vaginal Exfoliative Cytologysupporting
confidence: 88%
“…The shape of the superficial epithelial cells is an indicator that the cattle are in estrus. This is reinforced by [13] statement that superficial cells in vaginal swabs are a special marker for the presence of estrogen concentrations reaching 122.38 ng.mL. The results of the study are shown in table 2 that the percentage of intermediate on day 1 is dominant compared to parabasal and superficial.…”
Section: Variations In the Shape Of Vaginal Mucus Epithelial Cellsmentioning
confidence: 79%